Machiavellianism and learning-related subjective well-being among Chinese senior high school students: A moderated mediation model - Yang, Minqi; Qu, Chunyu; Guo, Hanxiao; Guo, Xicheng; Tian, Kexin; Wang, Guofang (Frontiers in Psychology, 2022)
To investigate the influence of Machiavellianism on the learning subjective well-being and the underlying mechanism, 582 Chinese senior high school students were recruited to participate in this study, and they anonymously filled out questionnaires regarding Machiavellianism, learning subjective well-being, gratitude, and subjective family economic level. The results showed that: (1) higher level of Machiavellianism was associated with lower level of learning subjective well-being; (2) gratitude partially mediated the relationship between Machiavellianism and learning subjective well-being; (3) subjective family economic level moderated the links between Machiavellianism and learning subjective well-being, and between gratitude and learning subjective well-being. This study explained how and when Machiavellianism affected Chinese senior high school students’ learning subjective well-being, and provided a deeper understanding of the relationship between Machiavellianism and learning subjective well-being.